The nutrient foramen of the humerus: Anatomical facts and clinical implications - Apichat Sinthubua (2018)
© 2017 Japan Health Sciences University & Japan International Cultural Exchange Foundation. Background: One of the main factors for non-union of fractures is inadequate blood supply. Hence, it is important to know the vascular supply of humerus, prior to any operative procedures. The nutrient arteries are important arteries which traverse the nutrient foramen to supply blood to the humerus. The present narrative review aims to look into the anatomical facts and clinical implications of the nutrient artery supplying the humerus. Methods: A thorough search of literature was done to retrieve articles related to the nutrient foramen of the humerus. Results: The position of the nutrient foramen, direction, number, and incidence in different sexes, and clinical importance with regard to designing flaps, operative procedures, were being highlighted in the present review. Conclusion: The anatomical knowledge of nutrient artery may be beneficial for orthopedic surgeons operating fractures, performing bone grafting, implants and designing vascular flaps.